Study Of The Effect Of Tax Revenues On GDP In Syria During The Period (1990-2017) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to study the Syrian tax reality in several stages while tracking the path of GDP under tax revenues during these stages, and the study used the descriptive analytical method of the theoretical framework with the use of linear regression as a statistical method to study the causal relationship between revenues Tax and GDP at current prices by using spps25.the study found a very strong linear correlation between total taxes and GDP during the period from 1990 to 2010, and a very weak linear correlation between total taxes and GDP during the period 1990-2010, and a very weak linear correlation between total taxes and GDP during the period The period of war on Syria.يهدف البحث إلى دراسة الواقع الضريبي السوري على عدة مراحل، مع تتبع مسار الناتج المحلي الإجمالي في ظل الإيرادات الضريبية خلال هذه المراحل، وقد استخدمت الدراسة المنهج الوصفي التحليلي للإطار النظري مع استخدام انحدار خطي كأسلوب إحصائي، لدراسة العلاقة السببية بين الإيرادات الضريبية والناتج المحلي الإجمالي بالأسعار الجارية باستخدام برنامجSPSS25 .وقد توصلت الدراسة إلى وجود علاقة ارتباط خطي قوي جداً بين إجمالي الضرائب والناتج المحلي الإجمالي خلال الفترة الممتدة من 1990-2010، وإلى وجود علاقة ارتباط خطي ضعيفة جداً بين إجمالي الضرائب والناتج المحلي الإجمالي خلال فترة الحرب على سورية.